Tracking Needs-Based Community and Specialized Services of Young Adults and Their Parents Before and During a First Episode of Psychosis (FEP): Highlighting Intervention Trajectories in FEP - Marie-Hélène Morin; Maryse Proulx (SAGE Publishing, 2023)
Aim: This article aims to document 10 service trajectories of young adults (YA) and their parents, informed by healthcare professionals (HP), before and during a first episode of psychosis (FEP). Design: Based on a crisis model perspective of the Life Course Theory (Elder; Elder and Shanahan) developed by Carpentier and White, and adapted to the current context to track community and specialized services trajectories. Thematic analysis was used to code responses to open-ended questions around the need for help and accessing services by young adults affected by a psychotic disorder, and their parents. Setting: In collaboration with FEP clinics, setting of choice by YA and their parents. Participants: 5 YA, 12 parents, and 6 HP. Results: 10 individual service trajectories grouped into 3 distinct types of trajectories (optimal, typical, and complex) based on grouping 5 similar characteristics, highlighting service access complexity and early intervention in FEP. Conclusion: This study is the first of its kind to examine the experiences of those who seek needs-based community and specialized services leading up to and during a FEP. Findings provide key insights related to early intervention in FEP and recommendations on improving access to such services in Quebec.